Variasi Penambahan Ekstrak Kulit Pisang Sebagai Sumber Antioksidan pada Produksi Tahu Putih - Hida Arliani Nur Anisa; Myra Wardati Sari; Yopi Wardati Riani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of adding plantain peel extract as a source of antioxidants on white tofu production. This research is an experimental research, while the research stages are; 1) Making banana peel extract; 2) Antioxidant Test of Banana Skin Extract; 3) Phytochemical test of banana peel extract; 4) Tofu production with a combination of banana peel extract with various concentrations of 5%, 10%, and 15%; 5) Extraction of fortified tofu; 6) Test the antioxidant activity of tofu; 7) ALT test. The results showed that the banana peel extract contained alkaloids, tannins, flavonoids, steroids, and triterpenoids. The antioxidant activity of the banana peel extract was 58.020%. The antioxidant activity value of the most optimum fortified tofu was shown in the addition of banana peel extract with a concentration of 15% with a shelf life of 1 day at room temperature which was 51.868%. The best ALT value was seen in tofu with variations in the addition of banana peel extract by 15% with a shelf life of 1 day at room temperature. In conclusion, the use of banana peel extract can not only increase the value of antioxidant activity but can improve the quality of the tofu by increasing the shelf life at room temperature. Keywords: ALT, banana peel extract, Tofu Production, Source of Antioxidants